Resurrection of the genus Homostylium Nees for the former Aster ser. Albescentes Y.Ling (Astereae, Asteraceae), with an updated generic synopsis - Xinyu Chen; Zhixi Fu (PhytoKeys)
Recent molecular phylogenetic studies have demonstrated extensive paraphyly of Aster ser. Albescentes Y.Ling. This woody-based shrubby group is both morphologically and molecularly distinct from the genus Aster L. The series is characterized by its shrubby habit with multiple branches, cauline leaves with revolute or flat margins, radiate capitula, keeled phyllaries, and multinerved achenes. We redefine a more natural circumscription of this series by reinstating Homostylium Nees with nomenclatural priority. A taxonomic synopsis of this series is presented herein. Homostylium is recognized and described as a distinct genus (Astereae, Asteraceae) to accommodate 7 shrubby species (6 endemic to China) formerly placed in Aster ser. Albescentes. A total of 19 new combinations are proposed, e.g., Homostylium albescens (DC.) Z.X.Fu, comb. nov. (incl. 10 varieties), Homostylium argyropholium (Hand.-Mazz.) Z.X.Fu, comb. nov. (incl. 2 varieties), Homostylium fulgidulum (Grierson) Z.X.Fu, comb. nov., Homostylium hypoleucum (Hand.-Mazz.) Z.X.Fu, comb. nov., Homostylium lavandulifolium (Hand.-Mazz.) Z.X.Fu, comb. nov., Homostylium motuoense (Y.L.Chen) Z.X.Fu, comb. nov., and Homostylium polium (C.K.Schneid.) Z.X.Fu, comb. nov. Formal typifications, synonyms, illustrations, distribution maps, and an identification key to the species of Homostylium are also provided herein.